2020
DOI: 10.1002/ente.202000106
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced Dry and Bireforming of Methane to Fuels over La‐Modified TiO2 in Fixed‐Bed and Monolith Reactors

Abstract: A systematic investigation on the performance of fixed‐bed and monolithic reactors for dynamic photoinduced CO2 reduction with CH4 via dry and bi‐reforming of methane over La‐modified TiO2 nanocatalyst under UV light is conducted. La/TiO2 is synthesized using a modified sol–gel method, and the monolithic‐coated catalyst is synthesized using a dip‐coating method. The performance of La/TiO2 is tested for different reforming systems in both types of photoreactors. The results reveal 5 wt% La/TiO2 effectively prom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…The photocatalysis process has great potential in promoting reactions that cannot occur in normal conditions . Reforming reactions, such as the dry reforming reaction, shown in eq , and bi-reforming reaction using water, shown in eq , require semiconductors with high oxidative photocatalytic activity for breaking the C–H bond of methane (CH 4 ) . Also, it needs higher ability of reduction for water splitting.…”
Section: Mxene As a Co-catalyst For Photocatalytic Flared Gas Reformingmentioning
confidence: 99%
See 1 more Smart Citation
“…The photocatalysis process has great potential in promoting reactions that cannot occur in normal conditions . Reforming reactions, such as the dry reforming reaction, shown in eq , and bi-reforming reaction using water, shown in eq , require semiconductors with high oxidative photocatalytic activity for breaking the C–H bond of methane (CH 4 ) . Also, it needs higher ability of reduction for water splitting.…”
Section: Mxene As a Co-catalyst For Photocatalytic Flared Gas Reformingmentioning
confidence: 99%
“…193 Reforming reactions, such as the dry reforming reaction, shown in eq 1, and bi-reforming reaction using water, shown in eq 2, require semiconductors with high oxidative photocatalytic activity for breaking the C− H bond of methane (CH 4 ). 194 Also, it needs higher ability of reduction for water splitting. Therefore, wide bandgap semiconductors comprising of strong redox potential for reforming technology are highly demanding.…”
Section: Mxene As a Co-catalyst Formentioning
confidence: 99%
“…The reason behind the higher activity can be attributed to a higher surface area, higher dispersion of the Ni catalyst, and a smaller particle size. On the basis of various studies it can be concluded that noble metals have strong resistance against carbon deposition; however, their cost limits application at an industrial scale. , It is suggested that for higher catalytic activity of Ni-based catalysts, the addition of noble and non-noble metals can be useful for enhanced catalytic performance of Ni catalysts with more resistance to carbon deposition. Other parameters such as support selection, preparation method, and catalyst promoter have greater potentials toward maximizing catalyst performance …”
Section: Natural Gas Flaring Utilization Technologiesmentioning
confidence: 99%
“…The preparation of syngas (CO, H 2 ) from photocatalytic CRM is also an important research topic, and many researchers have been making unremitting efforts to improve the quantum efficiency of the reaction process. [ 136–141 ] For example, Hu and co‐workers reported an efficient visible‐light photocatalytic CRM process by combining a Pt/black TiO 2 catalyst with the light‐reflecting surface of a SiO 2 substrate. [ 142 ] This process exhibits a high quantum efficiency of 32.3% at 550 °C and 57.8% at 650 °C under visible‐light irradiation ( Figure a,b).…”
Section: Photocatalytic Conversion Of Methanementioning
confidence: 99%